Sidewalks of New York - Schulman, Cathy; Yorn, Rock; Bridger, Margot; Burns, Edward 1968-; Burns, Edward 1968-; Burns, Edward 1968-; Dawson, Rosario 1979-; Farina, Dennis 1944-2013 (Paramount Home Video, 2001)
This film follows the marital and dating lives of three men and three women who unknowingly form a tangled web of relationships. The film weaves a humorous and biting commentary on the game of love-easy to start, hard to finish.